Unsteady MHD free convective flow past a vertical plate: An automated solution approach - Nor Raihan Mohamad Asimoni; Nurul Farahain Mohammad; Abdul Rahman Mohd Kasim (Research and Social Study Institute, 2021)
The case of unsteady two-dimensional laminar free convection flow over a vertical plate by an incompressible viscous fluid is analysed in the presence of uniform magnetic field perpendicular to the flow. The governing equations in a vector form are transformed into non- dimensional form. Then, the dimensionless equations are solved using automated solution technique which is FEniCS. The effects of magnetic parameter on the velocity and temperature profiles are obtained and discussed in this paper